A validade da Lei da Anistia e as decisões do Supremo Tribunal Federal e da Corte Interamericana de Direitos Humanos / The validity of Amnesty Law and the decisions taken by the brazilian Supreme Court and the Inter- American Court of Human Rights - de Niemeyer, Pedro Octavio (Revista Direito e Práxis, 2016)
DOI: 10.12957/dep.2016.18045 Resumo O presente artigo pretende um estudo comparativo entre duas decisões proferidas por Cortes de cúpula acerca do mesmo tema: a Lei da Anistia (L. 6.683/79). A aludida Lei teve sua constitucionalidade questionada no Supremo Tribunal Federal e foi, também, objeto de decisão sobre sua convencionalidade no âmbito da Corte Interamericana de Direitos Humanos. As decisões das Cortes apontaram em direções opostas. Palavras chave: Lei da anistia. Supremo Tribunal Federal. Corte Interamericana de Direitos Humanos. Abstract The present article intent to compare two decisions taken by High Courts about the same law: the brazilian Amnesty Law (L. 6.683/1979). On one hand, the brazilian Supreme Court decided that the law 6.683/1979 is valid under the Brazilian Constitution, on the other hand the Inter- American Court of Human Rights declared the brazilian Amnesty Law invalid under the American Convention on Human Rights (Pact of San Jose). The focus of this academic work is to study the uniqueness of the collision between two decision taken by High Courts about the validity of the same brazilian law. Keywords: Amnesty Law. ADPF 153/DF. Supreme Court of Justice. Inter-American Court of Human Rights. American Convention on Human Rights. Araguaia Guerrilha Movement . Gomes Lund and Others vs. Brazil. Law 6.683/1979.